Levodopa induces thyroid function regulation in a patient with thyroid hormone resistance and Parkinson’s disease: a case report - Rozo-Paz, Gabriela; Ruiz-Forero, Clara Maria; Suárez-Mera, José David; Monsalve Duarte, Guillermo; Kattah Calderón, William (Frontiers in Endocrinology, 2025)
IntroductionThyroid hormone resistance (THR) is a rare genetic syndrome characterized by reduced sensitivity to thyroid hormones. Patients may be asymptomatic, although clinical manifestations depend on the THR subtype. This entity commonly has abnormal thyroid function tests and can be confirmed by molecular analyses.Case presentationThe present study describes a 55 year-old female diagnosed with surgically resected papillary thyroid carcinoma. During the endocrinology consults, elevated thyroid hormone levels were detected without an adequate TSH response, and THR was suspected. Moreover, Parkinson’s disease was diagnosed, and treatment with levodopa/carbidopa was initiated. Following this regimen, her TSH and total T3 levels were subsequently normalized, which suggests a potential effect of this agent on the normalization of these hormone levels in the blood. In this case, the role of levodopa was crucial to regulate the TSH concentration which was required to carry out the resection of a tumoral remnant.ConclusionThe influence of dopamine in the endocrine system, specifically in the thyroid gland, is beneficial in conditions such as THR where abnormal TSH levels can be lowered, helping to balance the thyroid and hormones function.